1987
DOI: 10.1172/jci113193
|View full text |Cite
|
Sign up to set email alerts
|

Weight reduction increases adipose tissue lipoprotein lipase responsiveness in obese women.

Abstract: Lipoprotein lipase was measured in gluteal adipose tissue from nine obese (90.6±2.7 kg) women fasting and after the intravenous infusion of insulin and glucose before, immediately after, and 3 mo subsequent to a 14.0±1.8% (i±SEM) weight reduction. Fasting adipose tissue lipoprotein lipase activity (ATLPL) decreased from 5.3 to 2.3 nEq FFA/106 cells per mi (P < 0.02) immediately after weight reduction, yet after weight maintenance, higher levels were again found (6.1 nEq FFA/106 cells per min). Although respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 28 publications
2
38
1
Order By: Relevance
“…Our ®ndings in women, but not in men, are concordant with previous observations. 7,15,16 Indeed, one study exclusively composed of men 18 and another that included six men and three women 19 have already reported an increase in AT-LPL activity after weight loss. It is possible that such discrepancy could be due to the substantial mean weight loss (16 and 43 kg) reported in the two previous studies, as already hypothesized.…”
Section: Discussionmentioning
confidence: 99%
“…Our ®ndings in women, but not in men, are concordant with previous observations. 7,15,16 Indeed, one study exclusively composed of men 18 and another that included six men and three women 19 have already reported an increase in AT-LPL activity after weight loss. It is possible that such discrepancy could be due to the substantial mean weight loss (16 and 43 kg) reported in the two previous studies, as already hypothesized.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, infrequent eating concentrated in the evening may be involved in weight gain (Fricker et al 1990). This factor may be related to circadian changes in insulin secretion; insulin levels tending to be higher in the latter part of the day (Apfelbaum et al 1972), resulting in greater uptake of fatty acids by adipocytes (Eckel & Yost, 1987).…”
Section: How Could Frequent Eating Help Body-weight Control?mentioning
confidence: 99%
“…Hill et al (15) and Wheeler et al (39) found that AT-LPL activity is higher in weight cycled rats than in control rats both at the end of a weight cycling period and during the refeeding period. In obese humans, AT-LPL activity levels are elevated compared to normal weight controls (8,34). However, after weight reduction, AT-LPL levels are further elevated (30).…”
Section: Introductionmentioning
confidence: 99%